Development of a GnRH-PGF2α Based Synchronization and Superstimulation Protocol for Fixed-Time Mating in Llama Embryo Donors - Zampini, Enzo German; Veiga, Maria Fernanda; Fumuso, Fernanda Gabriela; Cabido, Luciana; Neild, Deborah Margarita; Chaves, Maria Graciela; Miragaya, Marcelo Horacio; Trasorras, Virginia Luz (Frontiers in Veterinary Science, 2020)
The aim of the present study was to evaluate the application of a GnRH-PGF2α based synchronization and superstimulation protocol for fixed-time natural mating in llama embryo donors. All females (n=8) received 8 µg IM of GnRH analogue (GnRHa; buserelin) on day 0, regardless of follicular status. After eight days, another GnRHa dose was administered followed by 250 µg IM PGF2α (cloprostenol). A dose of 1000 IU IM of equine chorionic gonadotrophin (eCG) was applied on day 12 and a new dose of PGF2α was administered on day 13. All embryo donors were mated with a male of proven fertility followed by a GnRHa dose on day 18. Twenty four hours later, mating was repeated with a different male. Transcervical uterine flushing for embryo recovery was carried out on all females on day 26. Recipient females received one dose of GnRHa (day 0) two days after the first mating of embryo donor females. A 75% (6/8) of embryo donors responded to the superstimulation treatment with a range of 2 to 5 corpus luteums (CLs) on embryo recovery day. A total of 24 CLs were registered, with a mean of 4 ± 0.9 CLs per female. Embryo recovery rate was 66.7% (16/24), with a range of 0 to 4 embryos and a mean of 2.7 ± 1.5 embryos per female. Regarding quality of the recovered embryos, 56.2% were grade I, 6.2% were grade II and 37.5% were grade V (untransferable; arrested morulae). Grade I and II embryos (n=10) were transcervically transferred into recipient females (n=10) six days after inducing their ovulation. At 24 days after embryo transfer (ET), a 50% pregnancy rate was registered. In conclusion, a group of llama embryo donors can be synchronized and superstimulated using a fixed-time mating protocol based on GnRHa, PGF2α and eCG without the necessity of using ultrasonography in the field.